Modern Reforms in Enhancing Higher Education Quality: Philosophical Foundations and Legal Frameworks - Jumaniyazova Nasiba Saparbaevna (Scientific Trends, 2025)
This article examines modern reforms in the higher education system of Uzbekistan, analyzing their philosophical foundations and legal frameworks. It highlights international experiences in educational quality assurance and the essential role of human capital in sustainable socio-economic development. Based on the Concept for the Development of Higher Education in Uzbekistan until 2030, the paper evaluates recent reforms, identifies existing challenges, and proposes recommendations for raising the quality of education to international standards.
Keywords: Higher education, educational reforms, educational quality, personnel training, educational policy, Uzbekistan.